2011
DOI: 10.1038/aps.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid attenuates multiorgan dysfunction in rats after heatstroke

Abstract: IntroductionHeatstroke is defined as a form of excessive hyperthermia (>40 °C) associated with a systemic inflammatory response that leads to multi-organ dysfunction in which central nervous system (CNS) disorders such as delusion, convulsion and coma predominate [1] . Our recent results have demonstrated that heatstroke rodents display hypotension, systemic inflammatory responses, hypothalamic ischemia and neuronal damage, and multi-organ dysfunction [2][3][4] .Kynurenic acid (KYNA) or its metabolic precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Interestingly, KYNA might exert a protective role on multiple organs during heatstroke through anti-inflammatory mechanisms [22]. Here, we found that the plasma levels of KYNA were significantly lower in Cbs +/− mice supplemented with methionine but trended higher after injection with AdDYRK1A (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Interestingly, KYNA might exert a protective role on multiple organs during heatstroke through anti-inflammatory mechanisms [22]. Here, we found that the plasma levels of KYNA were significantly lower in Cbs +/− mice supplemented with methionine but trended higher after injection with AdDYRK1A (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…During the course of bacterial meningitis, anti-inflammatory cytokines are produced to mitigate the induced inflammation [ 4 , 31 ]. Some studies have proposed that cells of the immune system use a bidirectional communication in which TRP catabolism through IDO activity drives the generation of IL-10-producing regulatory T-cells [ 8 , 9 , 18 , 19 ]. In BM patients, we observed a positive correlation between IDO activity and the inflammatory cytokines IFN-γ and IL-1Ra (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar data were obtained in a study carried out by Hsieh et al ., showing that KYNA improves the outcomes of heatstroke in rats. In this model, KYNA inhibited the expression of inflammatory molecules such as TNF-α and ICAM-1 and enhanced IL-10 levels [ 19 ]. Corroborating the findings regarding neuroprotection, the reduced production of KYNA in astrocytes has been proposed to increase neurological symptoms of cerebral malaria [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations